Scripts for logistic regression of ASE genomic determinants. - Benjamin Laenen (Stockholm University, 2016)
Script used in Steige et al. 2017 PNAS for estimating the impact of genomic features on allele specific expression in Capsella grandiflora using logistic regression.
* The folders contains an jupyter notebook (ypython) that runs the analysis by downloading the input from figshare   * A html reports of the analysis performed in the paper   * a r script from the jupyter notebook
Keywords: 60409 Molecular Evolution; Evolutionary Biology; Evolutionary Biology; Evolutionsbiologi; Biochemistry; Biokemi